Conditional cash transfers and embedded extension: A mechanism to restore and promote adoption of improved goat shelters in emergency recovery. (April 2021) - Kattel, Prachanda; Mohan, Krishna
Abstract: Reconstruction of damaged goat shelters was a key need for communities in the Gorkha district, which was the epicenter of the earthquake in 2015, as lack of shelters led to distress sale of goats and reduction in herd size. Additionally, existing shelters caused diseases in goats due to poor ventilation and hygiene features. Drawing on its global experience and expertise in livelihoods, cash, and markets especially in emergency situations, CRS supported conditional cash transfers, provided in two tranches (upon beneficiary choice and construction completion), along with extension (group orientations, mentoring) focused on shelter design principles, to help poor households critically depending on income from goats reconstruct hygienic goat shelters. CRS promoted two simple, cost-effective design principles while facilitating the reconstruction of goat shelters, i.e., a raised platform and provision for ventilation. A study was undertaken to assess the effectiveness of conditional cash transfers combined with a targeted extension on the adoption of improved goat shelter principles by earthquake-affected households, through 100% visual verifications, household surveys, focus group discussions (FGD) with beneficiaries and non-beneficiaries, and key informant interviews with stakeholders. The study reported that 99% of beneficiaries adopted the hygienic shelter principles promoted by the project based on the conditionality. Beneficiaries co-invested on an average of 80–100 in addition to the 100 received from the project. A 20–30% increase in herd size among most beneficiaries was reported after the reconstruction of goat shelters due to the availability of safe space. The study showed strong ownership by the beneficiaries which was evident from the maintenance and up-keeping of the goat shelters. Households, who had not received cash from the project, have also started adopting the design principles mainly due to the low-cost and simple nature of the design principles. Which project has provided them with flexibility in using the material of their choice based on the local context. Highlights: Extension embedded with cash transfer in goat shelter construction. Cash empowered HHs in material selection, ownership. Cash in two tranches crucial for upfront investment. Cash support nudged HHs for additional investment especially women. Identification of barriers perceived as crucial by communities led to strong engagement.